a PEWARNA ALAMI AKAR MENGKUDU (Morinda citrifolia L) SEBAGAI PENGGANTI SAFRANIN PADA PEWARNAAN GRAM NEGATIF - sari, sofiani (Deli Medical and Health Science Journal, 2024)
Noni is a plant that has the potential to be used as a therapeutic element, but many people are still unaware of its benefits. This plant is one of the herbal plants part of the noni plant has body parts that can almost all be utilised. Noni root or known as Morinda citrifolia L. can be processed and used as a natural dye because it contains morindon. Noni contains the molecule morindin, a disaccharide derivative of anthraquinone or anthraquinone, so its roots are used as a dye. Morindon is a natural dye produced when morindin glycoside is hydrolysed which will produce a red colour. Morinda citrifolia Linn fruit has antibacterial properties inherent in phenol and flavonoid molecules. The purpose of this study is to determine whether or not noni root extract can be used as an alternative to safranin gram staining. The variables used were noni root extract and gram staining which were carried out by Experimental Laboratories. This research began in May to June 2023. The results showed that noni root extract in a 60-second soak could colour gram-negative bacteria but in 20-second and 30-second soaks there was no red colour on gram-negative bacteria. Noni root extract can be applied as an alternative gram stain to safranin.